1988
DOI: 10.1002/1520-6629(198807)16:3<332::aid-jcop2290160308>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity and cultural diversity: An analysis of work published in community psychology journals, 1965–1985

Abstract: The purpose of this survey was to examine the extent to which community psychology has committed itself to one of its original missions: to foster cultural relativity and diversity. Content analyses were conducted of all articles published in the American Journal of Community Psychology, Community Mental Health Journal, and the Journal of Community Psychology from the journals' inception through 1985. Of all articles published, 13% furthered the goals of cultural diversity, and 86% did not. Further breakdown r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(58 citation statements)
references
References 12 publications
3
55
0
Order By: Relevance
“…For instance, almost 20 years ago Loo et al (1988) found that overall only 13% of the articles published between 1965 and 1985 in AJCP, the Community Mental Health Journal (CMHJ), and the Journal of the Community Psychology (JCP) attended to cultural relativity or cultural diversity; 17% within AJCP alone. They respectively defined cultural relativity and diversity as the within group study of a single ethnic group (e.g.…”
Section: Appreciation Of Diversitymentioning
confidence: 99%
“…For instance, almost 20 years ago Loo et al (1988) found that overall only 13% of the articles published between 1965 and 1985 in AJCP, the Community Mental Health Journal (CMHJ), and the Journal of the Community Psychology (JCP) attended to cultural relativity or cultural diversity; 17% within AJCP alone. They respectively defined cultural relativity and diversity as the within group study of a single ethnic group (e.g.…”
Section: Appreciation Of Diversitymentioning
confidence: 99%
“…In sum, it has been well documented that research on White populations outnumbers research on ethnic or culturally diverse populations (Fisher, Jackson, & Villarruel, 1998;Graham, 1992;Loo, Fong, & Iwamasa, 1988), which limits our understanding of how cultural differences may affect development, beliefs, ideas, and behaviors in ethnic minority adolescent populations. Furthermore, research exploring intragroup differences has been almost nonexistent and, when conducted, has not typically been founded on theoretical bases.…”
Section: Cognitive Representations Of Peer Relationshipsmentioning
confidence: 99%
“…Like Loo et al. (), Bernal and Enchautegui‐de‐Jesus () established that the representation of these groups fell well below their overall proportion in the U.S. population. They argued that the comparative paucity of diversity‐related articles, especially among specific underserved groups, indicated a gap between the ideals and practice of community psychology (Bernal & Enchautegui‐de‐Jesus, ).…”
Section: Social Exclusion In the Study Of Empirical Researchmentioning
confidence: 91%
“…Although Loo et al. () also reported an increase in cultural diversity over 20 years (from 5.5% to 11%), they illustrated that the representation of cultural minorities still fell well below the proportion of these groups within the U.S. population (of over 20%). They concluded that progress was evident in promoting cultural diversity in published work, but they held that more needed to be done to ensure that the underrepresented did not remain on the margins (Loo et al., ).…”
Section: Social Exclusion In the Study Of Empirical Researchmentioning
confidence: 95%